PENGARUH PEMBIAYAAN, NON PERFORMING FINANCING (NPF), CAPITAL ADEQUACY RATIO (CAR), DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS BANK SYARIAH - Hasanah, Uswatun; Made, Anwar; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2019)
The purpose of this study was to examine and determine the effect of Financing, Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) on the Profitability of Islamic Banks in Indonesia in 2013-2017. The population of this research is Sharia Commercial Bank in Indonesia. Sampling uses the time series cross section method. The population is 11 Sharia Commercial Banks. Methods of observation for 5 years (2013-2017). Analysis of the data used in research is the classic assumption test and hypothesis test. The method used in this research is quantitative descriptive method, and the analytical method used is multiple linear regression analysis. The results of the study show that the Non Performing Financing (NPF) and Capital Adeaucy Ratio (CAR) variables affect the profitability of Islamic Commercial Banks both partially and simultaneously whereas for Financing and Financing to Deposit Ratio (FDR) variables do not partially affect the Sharia Commercial Bank Profitability.